Assessment of Knowledge and Attitude about Traumatic Dental Injuries First Aid of Faculty Members and Undergraduate Bachelor in Physical Education in the UP College of Human Kinetics of A.Y.2021-2022/ Mary Allyson B. Campos, Jeanne Louise S. de Paz and Kristina Patricia D. dela Rosa. - Campos, Mary Allyson B.
INTRODUCTION: Traumatic dental injury (TDI) is an injury of the hard and soft tissues in the oral cavity by its collision with any object. Sports poses a greater risk of having TDIs, necessitating a need for Physical Education and sports-related professionals to know immediate measures after it happens in school and sports.